FACTORS THAT INFLUENCE STUDENTS’ DECISION TO DROPOUT OF ONLINE COURSES - Pedro A. Willging; Scott D. Johnson (Online Learning, 2019)
Although there are many reasons why students dropout of college courses, those reasons may be unique for students who are enrolled in an online program. Issues of isolation, disconnectedness, and technological problems may be factors that influence a student to leave a course. To understand these factors, an online survey was developed to collect data from students who dropped out of an online program. Logistic regression analysis was used to compare various factors between those who persist in the program and those who dropout. The results, based on the dropouts from three cohorts in an online graduate program, show that demographic variables do not predict likelihood of dropping from a program. Instead, the students’ reasons for dropping out of an online program are varied and unique to each individual. Recommendations for further study are incorporated in the conclusions.